Empagliflozin in acute myocardial infarction in patients with and without type 2 diabetes: a pre-specified analysis of the EMPACT-MI trial - Petrie, Mark C.; Udell, Jacob A.; Anker, Stefan D.; Harrington, Josephine; Jones, W. Schuyler; Mattheus, Michaela; Gasior, Tomasz; van der Meer, Peter; Amir, Offer; Bahit, M. Cecilia; Bauersachs, Johann; Bayes-Genis, Antoni; et al. (European journal of heart failure, 2024)
Aims In the EMPACT-MI trial, empagliflozin reduced heart failure (HF) hospitalizations but not mortality in acute myocardial infarction (MI). Contemporary reports of clinical event rates with and without type 2 diabetes mellitus (T2DM) in acute MI trials are sparse. The treatment effect of empagliflozin in those with and without T2DM in acute MI is unknown. Methods and results A total of 6522 patients with acute MI with newly reduced left ventricular ejection fraction (LVEF) to <45%, congestion, or both, were randomized to empagliflozin 10 mg or placebo. The primary endpoint was time to first HF hospitalization or all-cause death. Rates of endpoints with and without T2DM and the efficacy and safety of empagliflozin according to T2DM status were assessed. Overall, 32% had T2DM; 14% had pre-diabetes; 16% were normoglycaemic; 38% had unknown glycaemic status. Patients with T2DM, compared to those without T2DM, were at higher risk of time to first HF hospitalization or all-cause death (hazard ratio [HR] 1.44; 95% confidence interval [CI] 1.06-1.95) and all-cause death (HR 1.70; 95% CI 1.13-2.56). T2DM did not confer a higher risk of first HF hospitalization (HR 1.22, 95% CI 0.82-1.83). Empagliflozin reduced first and total HF hospitalizations, but not all-cause mortality, regardless of presence or absence of T2DM. The safety profile of empagliflozin was the same with and without T2DM. Conclusion Patients with acute MI, LVEF <45% and/or congestion who had T2DM were at a higher risk of mortality than those without T2DM. Empagliflozin reduced first and total HF hospitalizations regardless of the presence or absence of T2DM.
Erstmals veröffentlicht: 26. Dezember 2024
Gesehen am 25.03.2025